Realizations of deonticity in Lithuanian: The case of particles - Jasionytė-Mikučionienė, Erika; Ruskan, Anna (Vilnius University Open Series, 2021)
The present paper focuses on non-epistemic modal particles in contemporary Lithuanian that have received far less attention in the literature than epistemic particles. Based on authentic data drawn from the Corpus of the Contemporary Lithuanian Language, the study aims to disclose the formal and functional features of the particles tegu(l), te and lai in spoken discourse and fiction. The study has shown that the particles under investigation occur in hortative constructions where they express the speaker’s desire to get a third person or the addressee to carry out some action. Although tegu(l), te and lai share a number of functions (e.g. hortatives, negative or positive performative optatives), functional extension is more typical of tegu(l) than of te and lai. The formal features of the particles (their co-occurrence with indicative or subjunctive forms) provide evidence for their functional variation.